Kindergarten class. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows young evacuees in the kindergarten room at Portland, Oregon Assembly Center. Kindergartners are cutting paper dolls under supervision of Japanese teachers. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.